2020
DOI: 10.3390/ijms21083000
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1β Positively Regulates NF-κB Activity via Direct Control of TRAF6

Abstract: NF-κB signalling is crucial for cellular responses to inflammation but is also associated with the hypoxia response. NF-κB and hypoxia inducible factor (HIF) transcription factors possess an intense molecular crosstalk. Although it is known that HIF-1α modulates NF-κB transcriptional response, very little is understood regarding how HIF-1β contributes to NF-κB signalling. Here, we demonstrate that HIF-1β is required for full NF-κB activation in cells following canonical and non-canonical stimuli. We found that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Moreover, exogenous TRAF6 expression is capable to recover all of the cellular hypoxic phenotypes in absence of HIF-1β. These findings elaborated that HIF-1β is an essential regulator of NF-κB ( 37 ). Therefore, the inhibition of HIF-1β by SD3 may provide not only a role in the inhibition of the hypoxia pathway but also a suppression of the NF-κB activation process, a suggestion that needs further investigations.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, exogenous TRAF6 expression is capable to recover all of the cellular hypoxic phenotypes in absence of HIF-1β. These findings elaborated that HIF-1β is an essential regulator of NF-κB ( 37 ). Therefore, the inhibition of HIF-1β by SD3 may provide not only a role in the inhibition of the hypoxia pathway but also a suppression of the NF-κB activation process, a suggestion that needs further investigations.…”
Section: Discussionmentioning
confidence: 66%
“…PHD2 and PHD3 also reduce HIF activity by participating in the degradation of HIF-α subunits. Another mechanism is the involvement of HIF-1β in TNF receptor associated factor 6 (TRAF6) expression and therefore in NF-κB activation [ 143 ]. HIF-1α decreases TRAF6 expression, probably by binding HIF-1β into the HIF-1 complex.…”
Section: Chronic Hypoxiamentioning
confidence: 99%
“…It has been previously reported that the occurrence of IRI involves a variety of factors, and the damage caused by inflammatory response to cells is an important pathological mechanism (12). NF-κB, as an inflammation marker, is involved in the occurrence of various diseases, such as chronic inflammatory diseases, heart disease and cancer (13,14). NF-κB signaling regulates the immune response, hypoxia response, apoptosis and embryonic development, as well as tumorigenesis and development (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB, as an inflammation marker, is involved in the occurrence of various diseases, such as chronic inflammatory diseases, heart disease and cancer (13,14). NF-κB signaling regulates the immune response, hypoxia response, apoptosis and embryonic development, as well as tumorigenesis and development (12)(13)(14). TNF-α serves an important role as a proinflammatory cytokine in NF-κB-mediated inflammation (15).…”
Section: Introductionmentioning
confidence: 99%